Analisis Hubungan Peranan Orang Tua Siswa Kelas VII-T di MTsN 3 Jombang - Wardani, Dian Kusuma; Chikmah, Evi Laily Zakiyatul; Umardiyah, Fitri (Exact Papers in Compilation (EPiC), 2022)
In determining the student learning process there are many factors that influence but globally there are two important factors, namely internal factors (which exist within the students themselves) including physiological and psychological factors and external factors (from outside students) including environmental, instrumental and approach factors study. The purpose of this study was to determine the relationship between the roles of parents in class VII-T MTsN 3 Jombang. In this study, a sample of 39 students was taken. This research is a quantitative research and data is taken through a questionnaire, then the analytical tool used is correlation analysis. The variables used are the role of parents including the educational background of parents (X1), financial arrangements for children's education (X2), children's study time arrangements (X3), supervision of children's health (X4) and the provision of children's learning facilities (X5). The results obtained as follows that all variables have a value of r count > r table = 0.316. So it can be said that there is a significant relationship between the role of parents of class VII-T students at MTsN 3 Jombang.